Investigating static water uptake characteristics and mechanisms for leather and synthetic association footballs - Phillips, I.; Harland, A.; Mitchell, S.; Lepper, P. (Sports Engineering, 2025)
In association football, players repetitively head the ball for competitive advantages, potentially inducing or exacerbating repetitive acute asymptomatic brain injury pertaining to an elevated risk of neurodegenerative disease development and mortality in later life. During these collisions, the mass of the ball is widely considered an important determinant to collision duress. Many anecdotes cite differences in water uptake characteristics between modern and historical balls, but this has never been scientifically investigated. This study sought to investigate water uptake for a range of leather and synthetic balls. This study exposed seven football types, representative of those used through history, to static whole ball and specimen wettability measurements. All balls demonstrated water uptake. Stitched balls showed more uptake than stitchless balls, and leather balls showed greater uptake than synthetic balls. The magnitude of measured water uptake in leather balls corroborated with historical testing data and showed no evidence of balls doubling in mass, as speculated. All footballs showed similar discharge characteristics. Wettability studies showed greater rate of contact angle changes in leather balls. From differences between stitched and stitchless synthetic balls, two mechanisms of uptake were proposed: absorption (into panel material) and ingress (between panels). This work provides contextual significance to discussions surrounding the historical mass of the ball.